The Relationship of ABCB1/MDR1 and CYP1A1 Variants with the Risk of Disease Development and Shortening of Overall Survival in Patients with Multiple Myeloma - Szymon Zmorzynski (MDPI AG, 2021)
(1) Background: The aim of our study was to analyze the possible relationship of ABCB1 and CYP1A1 gene variants with susceptibility and outcome of multiple myeloma (MM); (2) Methods: Genomic DNA samples from 110 newly-diagnosed MM patients and 100 healthy blood donors were analyzed by methods-PCR-RFLP (for ABCB1 3435C > T, CYP1A1 6235T > C—m1), automated DNA sequencing (for ABCB1 1236C > T, 2677G > T/A) and allele-specific PCR (for CYP1A1 4889A > G—m2); (3) Results: The genotypic frequencies of CYP1A1 4889A > G variant were not in Hardy-Weinberg equilibrium for MM patients. The presence of m1 and m2 CYP1A1 alleles decreased the risk of MM—OR = 0.49 (p = 0.011) and OR = 0.27 (p = 0.0003), respectively. In turn, TT genotype (ABCB1 2677G > T/A) increased the risk of this disease (p = 0.007). In the multivariate Cox analysis CT + TT genotypes (ABCB1 3435C > T) were associated with decreased risk of death (HR = 0.29, p = 0.04). In log-rank test in patients with CT genotype (ABCB1 3435C > T) was observed association of overall survival with the type of treatment; (4) Conclusions: Our findings suggest that T-alleles of ABCB1 2677G > T/A and m1/m2 alleles of CYP1A1 affected the susceptibility of MM. Moreover, T-allele of ABCB1 3435C > T might be independent positive prognostic factor in MM.